Day-ahead Coordinated Operation of a Wind-Storage System Considering Wind Forecast Uncertainty - Nguyen, N. T. A.; Le, D. D. (Engineering, Technology & Applied Science Research, 2021)
This paper proposes an optimal operation for coordinated Battery Energy Storage (BES) and wind generation in a day-ahead market under wind uncertainty. A comprehensive AC Optimal Power Flow (AC OPF) model was established to incorporate wind and storage into a power system. To take into account wind forecast uncertainty, preprocessing technique, time series model, and fast forward selection method were applied for scenario generation and reduction processes. Tests were performed on a modified IEEE 14-bus system and the results show that the use of BESs is an alternative to guarantee a more efficient and flexible operation of wind power plants.